2018
DOI: 10.1016/j.tips.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Cancer: Regulation by Small Molecules

Abstract: During times of stress, autophagy is a cellular process that enables cells to reclaim damaged components by a controlled recycling pathway. This mechanism for cellular catabolism is dysregulated in cancer with evidence indicating that cancer cells rely on autophagy in the hypoxic and nutrient-poor microenvironment of solid tumors. Mounting evidence suggests that autophagy plays a role in the resistance of tumors to standard-of-care therapies. There is therefore significant interest in the discovery of small mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 78 publications
(83 reference statements)
1
58
0
Order By: Relevance
“…In addition, MRT68921 treated cells show significant increase in SQSTM1 level and decrease in LC3-2/LC3-1 ratio. These results suggested that MRT68921 treatment efficiently inhibits ULK-mediated autophagy [77] . However, the molecular basis of this block remains to be elucidated.…”
Section: Unc-51-like Kinases Inhibitorsmentioning
confidence: 75%
“…In addition, MRT68921 treated cells show significant increase in SQSTM1 level and decrease in LC3-2/LC3-1 ratio. These results suggested that MRT68921 treatment efficiently inhibits ULK-mediated autophagy [77] . However, the molecular basis of this block remains to be elucidated.…”
Section: Unc-51-like Kinases Inhibitorsmentioning
confidence: 75%
“…CQ and its analog, hydroxychloroquine (HCQ), are the only autophagy inhibitor being used for treating cancer in clinical trials 33 . However, Phase I/II clinical trials with CQ and HCQ showed mixed results with varying levels of efficacy, highlighting the needs to develop alternative autophagy inhibitors [33][34][35] . Numerous studies have indicated that GLP inhibits tumorigenesis through inducing apoptosis, inhibiting invasion, and regulating immune response 3,5,8 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is not clear to what extent lysosome regulation per se contributes to the tumorigenic role of AMPK in vivo. Genetic or pharmacologic inhibition of lysosomal function could help address this issue (Limpert et al, 2018). Furthermore, what might be the relevant outputs of lysosomal function in this context?…”
mentioning
confidence: 99%